Penanganan Malaria pada Pandemi COVID-19 - Syafarinah Nur Hidayah Akil (PROCEEDING UMSURABAYA, 2020)
AbstractThe current COVID-19 pandemic has caused more than 1 million deaths, with more than 37million cases known worldwide. This condition affects health management, including malariainfection. There is a possibility that malaria's morbidity and mortality may increase due tobarriers to access to health facilities. This article aims to discuss malaria control in theCOVID-19 pandemic, including the adaptation of service procedures in Indonesia. The directresponse to COVID-19 must be integrated with malaria control efforts. Access to malariaservices must be ongoing, and malaria control such as the distribution of insecticide-treatedbed nets must still be done. Surveillance activities can be carried out while still paying attentionto the use of PPE according to the protocol for preventing the transmission of COVID-19.Keywords: covid-19, malaria, malaria control